Smoking causes the disorder of glucose metabolism under different levels of blood pressure in male occupational population - Dan Wang; Deren Qiang; Wenchao Xu; Jiaqi Wang; Jiali Liu; Yu Qin; Yongqing Zhang; Qizhan Liu; Quanyong Xiang (The Journal of Clinical Hypertension, 2022)
Abstract Smoking is an important modifiable factor in the risk of type 2 diabetes. Type 2 diabetes and hypertension overlap in the population. The present study investigated effects of smoking on glucose metabolism under different blood pressure (BP) levels in occupational population. A smoking survey among occupational groups was conducted in 2018. The general linear model was used to analyze the differences of glucose metabolism indexes and BP indexes influenced by different smoking intensity (never 0, mild <10, moderate <20, heavy ≥20 pack‐years). Odds ratios of developing diabetes and β‐cell deficiency were analyzed by using logistic regression model. BP was further taken into account in the relationship between smoking and glucose metabolism. As a result, 1730 male workers aged 21 to 60 years were included in the analysis finally. Compared to never smokers, heavy smokers had significantly increased fasting plasma glucose. Moderate and above smokers had significantly increased glycosylated hemoglobin, decreased fasting plasma insulin and β‐cell function, after adjustment for covariates. Further, smoking intensity was found to have a dose‐dependent relationship with impaired β‐cell function and diabetes. In conclusion, smoking has a positive dose‐dependent relationship with β‐cell deficiency and diabetes. Male smoking workers, especially the moderate or higher smoking, with high‐normal and high BP levels are at high risk of abnormal glucose metabolism.